INDONESIAN INTELLECTUAL RIGHTS LAW PERSPECTIVE: COPYRIGHTS AS A FIDUCIARY COLLATERAL - Daniel Hendrawan; Ranti Fauza Mayana (Faculty of Law, Maranatha Christian University, 2018)
The development of the business world and investment is very fast. Many people want to invest, but sometimes are constrained by the capital they have. One of the ways to obtain omdal is to pledge copyright. Indonesia has Law of the Republic of Indonesia Number 19 Year 2002 About Copyright. In this law copyright has not been considered as a guaranteed item. Along with the development of the era, the government is deemed necessary that copyright can be categorized as objects that can be guaranteed. With the issuance of this new law, one way to obtain capital is to pledge copyright as an object with a fiduciary guarantee institution.